Prevalence and influencing factors of suboptimal health among urban middle-aged and elderly residents in China - Zi-cheng ZHANG; Yun-lian XUE; Jun XU (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To examine the prevalence and influencing factors of suboptimal health among urban middle-aged and elderly residents and to provide evidence for health promotion in the population. Methods Using stratified multistage random sampling, we recruited 3 600 urban permanent residents aged 45 years and above in five provinces across China and carried out a survey with Sub-Health Measurement Scale Version 1.0 and a self-designed questionnaire during December 2017 - October 2018. Unconditional multivariate logistic regression was adopted to explore influencing factors of suboptimal health status of the participants. Results Among 3476 participants completing the survey, the detection rate of general suboptimal health was 66.51% and the detection rate of physical, mental, and social suboptimal health status were 67.17%, 63.98%, and 69.45%, respectively. The results of unconditional multivariate logistic regression analysis revealed that with higher exposure to second-hand smoke, having unhealthy dietary behavior, and experiencing stress event during past six months were risk factors for suboptimal health; while, being married, with a monthly household income of 2 500 - 7 500 RMB yuan per capita, going to bed early and on time, with high adversity quotient, and paying a close attention to self-health were protective factors against suboptimal health. Conclusion Among urban permanent residents aged 45 years and above in China, the detection rate of suboptimal health status was relatively high, and mainly influenced by marital status, monthly household income per capita, second-hand smoke exposure, unhealthy eating habits, sleeping on time, adversity quotient, attention to self-health and recent stressful life event.